2014
DOI: 10.7454/mst.v18i1.2937
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Soy-Based Polyurethane Foam with Utilization of Ethylene Glycol in Polyol

Abstract: The use of vegetable oils on replacing petroleum has attracted attention of many researchers. The chemical structure of vegetable oils are different from petrochemicals, so the structure of soybean oil has to be chemically modified through its unsaturated fatty acid chain in triglyceride. A two step process was conducted for the preparation of soy-polyol in designated temperatures; 50 °C, 60 °C, and 70 °C. Ethylene glycol (EG) as co-reagent was taking part in soy-polyol synthesis, and the soy-polyol was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…The epoxide ring opener compounds that comply with the requirements of polyols as raw materials for making flexible polyurethane foam must have a hydroxyl number of less than 100 mg KOH/g, an acid number of less than 2 mg KOH/g and a low viscosity (Firdaus, 2014;Ionescu, 2016). The Dow Chemical Company has produced commercial polyol with a hydroxyl number of 56 mg KOH/g as a raw material for flexible polyurethane foam (The Dow Chemical Company, 2022).…”
Section: Hydroxyl Numbermentioning
confidence: 99%
“…The epoxide ring opener compounds that comply with the requirements of polyols as raw materials for making flexible polyurethane foam must have a hydroxyl number of less than 100 mg KOH/g, an acid number of less than 2 mg KOH/g and a low viscosity (Firdaus, 2014;Ionescu, 2016). The Dow Chemical Company has produced commercial polyol with a hydroxyl number of 56 mg KOH/g as a raw material for flexible polyurethane foam (The Dow Chemical Company, 2022).…”
Section: Hydroxyl Numbermentioning
confidence: 99%
“…Busa padat adalah busa yang memiliki kerapatan dengan nilai < 0,3 g/cm 3 (Lacoste et al, 2015). Kerapatan (density) adalah faktor utama dalam menentukan sifat suatu bahan terutama kekuatan mekaniknya (Firdaus, 2014).…”
Section: Hasil Dan Pembahasan 31 Kerapatan Busaunclassified
“…The denser the foam, the tighter the pore structure so that the ability to conduct heat gets higher. (Firdaus, 2014) reported that the density value determines the value of the mechanical strength of foam, where the higher the density value correlated with good mechanical strength. Table 2 shows that the values of gambier foam compressive strength follow the same pattern as the density and thermal conductivity values which increase with increasing gambier concentrations.…”
Section: Foam Density (G/cm 3 )mentioning
confidence: 99%